2021
DOI: 10.12775/eq.2022.004
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Oryza sativa L. with agri-food waste to improve the dietary value of crops

Abstract: Due to the low dietary value of crops, Zn-deficient soils and insufficient intake of other minerals, soil fortification is often necessary. Fortification is defined as the addition of one or more crucial nutrients to a food to reduce poverty in a population or specific population groups. Currently available technologies for rice fortification with vitamins and minerals are high-energy and time-consuming methods. Therefore, mineral enrichment of crops has received much attention from scientists. The originality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…This is justified by the fact that natural resources are limited and society strives for stable development. The most pressing issues are in the areas of natural water use (Sawicka et al, 2023;Hulai et al, 2022;Vambol et al, 2019), waste management (Ziarati et al, 2022;Husain Khan et al, 2023) and the creation of alternative energy (Constantinescu et al, 2018). Moreover, in these difficult and sometimes problematic issues there is a relationship, such as antibiotic-contaminated sewage sludge (Aly, 2016) and waste can be, in one way or another, converted into energy resources (Vambol et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This is justified by the fact that natural resources are limited and society strives for stable development. The most pressing issues are in the areas of natural water use (Sawicka et al, 2023;Hulai et al, 2022;Vambol et al, 2019), waste management (Ziarati et al, 2022;Husain Khan et al, 2023) and the creation of alternative energy (Constantinescu et al, 2018). Moreover, in these difficult and sometimes problematic issues there is a relationship, such as antibiotic-contaminated sewage sludge (Aly, 2016) and waste can be, in one way or another, converted into energy resources (Vambol et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to fortification, biofortification is cost-effective as it is a one-time investment to develop a biofortified crop and recurrent costs are low ( Shoab and Hefferon, 2022 ). Biofortified crops hold a brighter future to address nutritional challenges ( Yadav et al, 2020 ; Buturi et al, 2021 ; Mushtaq and Nazir, 2021 ; Ziarati et al, 2021 ). Biofortification is considered a sustainable and long-term solution to provide micronutrient-rich crops to people ( Bouis and Welch, 2010 ; Bouis and Saltzman, 2017 ; Garg et al, 2018 ; Heck et al, 2020 ; Van Der Straeten et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water is essential to sustain life on the biosphere (Zobeidi et al, 2022;Khan et al, 2020) However, with the increasing population and industrial growth, its resources are becoming limited and/or contaminated (Han & Currell 2022;Ziarati et al, 2022). Boretti and Rosa (2019) reported that one third of the world's population would experience severe water scarcity within the next 20 years.…”
Section: Introductionmentioning
confidence: 99%